1985
DOI: 10.1099/0022-1317-66-5-1105
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interferon Induction in Mice of Resistant and Susceptible Strains during Murine Cytomegalovirus Infection

Abstract: SUMMARYComparison of the induction of plasma interferon (IFN) by murine eytomegalovirus (MCMV) in BALB/c and CBA mice demonstrated similar kinetics of induction with maximum titres at 6 and 48 h after infection. Although neutralized by antibody to type I (~ and fi) IFN, the IFN was predominantly acidqabile. The 6 h titre was markedly dependent upon the dose and method of preparation of MCMV and also the strain of mouse used. Higher plasma IFN titres were found in CBA than in BALB/c mice tbllowing both intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…In both the highly resistant CBA/CaH, and moderately resistant C57BL/10 mouse strains, in vivo depletion of T cells did not affect the replication of MCMV in either the spleen or liver. The replication of MCMV within the visceral organs of CBA/CaH mice is thought to be controlled before the T cell response is fully activated, by mechanisms such as the level of susceptibility of individual target cells to infection by MCMV (Price et al, 1987(Price et al, , 1990; the production of IFN-~/fl (Allan & Shellam, 1985) and the action of NK cells . Similarly, studies using either NK cell deficient C57BL/6 beige mice (Shellam et al,198I), or C57BL/6J mice selectively depleted of NK cells (Bukowski et al, 1983;Scalzo et al, 1992;Shanley, i990;Welsh el al., 1990), have demonstrated that NK cells are primarily responsible for the control of MCMV replication in the spleens and livers of C57BL/6J mice during the early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the highly resistant CBA/CaH, and moderately resistant C57BL/10 mouse strains, in vivo depletion of T cells did not affect the replication of MCMV in either the spleen or liver. The replication of MCMV within the visceral organs of CBA/CaH mice is thought to be controlled before the T cell response is fully activated, by mechanisms such as the level of susceptibility of individual target cells to infection by MCMV (Price et al, 1987(Price et al, , 1990; the production of IFN-~/fl (Allan & Shellam, 1985) and the action of NK cells . Similarly, studies using either NK cell deficient C57BL/6 beige mice (Shellam et al,198I), or C57BL/6J mice selectively depleted of NK cells (Bukowski et al, 1983;Scalzo et al, 1992;Shanley, i990;Welsh el al., 1990), have demonstrated that NK cells are primarily responsible for the control of MCMV replication in the spleens and livers of C57BL/6J mice during the early stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the re[aLive importance of natural killer (NK) cell activity, interferon (IFN) production and virusspecific T cell responses in the control of MCMV infection correlate with genotype in certain cases. Thus, in the resistant CBA/CaH and moderately resistant C57BL/6J and C57BL/I0 strains early protective mechanisms such as IFN production [Allan & Shellam, 1985;Grundy (Chalmer) et al, 1982] and NK cell activity Bukowski et al, 1984;Shellam et al, 1985) control infection within 48 h of infection, before T cell responses reach maximum activity. In contrast, the more susceptible BALB/c mice rely on CD8 ÷ T cellmediated immunity for the control of MCMV infection (Reddehase et at, I985, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Interferon titres were determined by reduction of the c.p.e, caused by encephalomyocarditis virus on L929 cells as described elsewhere (Allan & Shellam, 1985). A mouse interferon standard (G-002-904-511) was included in every assay and had a mean titre of 1.2 x 104 international reference units/ml (NIH, Bethesda, Md., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…CBA (H-2'') mice survive challenge with 20-fold higher doses of MCMV than are tolerated by BALB/c (H-2'') mice. This is attributed to the intrinsic resistance of H-2'' cells to MCMV infection [32] and effective interferon [33] and NK cell responses [34].…”
Section: Discussionmentioning
confidence: 99%